PERANCANGAN SISTEM PENAWARAN STARTUP DAN INVESTOR ONLINE - Grace Levina Dewi; Suhatati Tjandra; Setya Ardhi; Alfira Jessica (SINTECH (Science and Information Technology) Journal, 2021)
In terms of establishing and nurturing startups, finances are required to ensure their long-term viability. Startups at this stage require the support of investors as financial backers. The dearth of forums for promoting companies makes it difficult for developers to get traction and attract investors. The bidding method for entrepreneurs and investors was designed with these limits in mind. The waterfall concept is used in the design of this offering system, in which the website design is completed consecutively from beginning to end. The purpose of this website's design is to make it easier for developers to advertise startups or "products," to create possibilities for developers to meet investors indirectly, and to make it easier for investors to analyze startups with future potential. Startups are classified according to their valuation value; the Discounted Cash Flow approach was used to calculate the valuation for this website design